Nasal unsedated seated percutaneous endoscopic gastrostomy (nuPEG): a safe and effective technique for percutaneous endoscopic gastrostomy placement in high-risk candidates - McCulloch, Adam (Frontline Gastroenterol, 2018)
OBJECTIVE: Percutaneous endoscopic gastrostomy (PEG) tube placement is associated with a high risk of cardiorespiratory complications in patients with significant respiratory compromise. This study reports a case series of high-risk patients undergoing PEG placement using a modified technique—nasal unsedated seated PEG (nuPEG) placement. DESIGN: Retrospective review of 67 patients at high risk of complications undergoing PEG placement between September 2012 and December 2016. SETTING: UK specialist tertiary centre for clinical nutrition support. INTERVENTIONS: Patients underwent ‘push’ PEG placement using nasal endoscopy without sedation in a seated position. MAIN OUTCOME MEASURES: Procedural success and tolerability, short term (within 24 hours), medium term (24 hours to 30 days) complications and survival were recorded. RESULTS: 67 patients underwent 68 nuPEG placements. The majority had motor neuron disease (46/67). One patient developed a lower respiratory tract infection the following day. Two patients experienced accidental displacement of their PEG within 2 weeks. One patient died within 30 days of nuPEG insertion due to reasons unrelated to the procedure. Endoscopic comfort scores of 1 or 2 (98.0%) indicated good tolerance. A failure rate of 10.5% was attributed to intrathoracic displacement of the stomach, almost certainly due to the advanced stage of the neurological disease and associated diaphragmatic weakness. CONCLUSIONS: Our experience with the nuPEG technique suggests that it is safe and well tolerated in high-risk patients. As a result, it has now entirely supplanted radiologically inserted gastrostomy insertion in our institution and we recommend it as the method of choice for gastrostomy tube insertion in such patients.